2017
DOI: 10.1186/s40360-017-0171-4
|View full text |Cite
|
Sign up to set email alerts
|

Haloperidol affects bones while clozapine alters metabolic parameters - sex specific effects in rats perinatally treated with phencyclidine

Abstract: BackgroundThe presentation of schizophrenia (SCH) symptoms differs between the sexes. Long-term treatment with antipsychotics is frequently associated with decreased bone mineral density, increased fracture risk and metabolic side effects. Perinatal phencyclidine (PCP) administration to rodents represents an animal model of SCH. The aim of this study was to assess the effects of chronic haloperidol and clozapine treatment on bone mass, body composition, corticosterone, IL-6 and TNF-α concentrations and metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 106 publications
1
6
0
Order By: Relevance
“…In studies carried out in animal models, similar effects to those described above in cell cultures have been observed in MQs. In a perinatal phencyclidine rat model, the administration of clozapine increased IL-6 and TNF-α with sex-specific changes (91), which can fit in the theory of "cytokine signature" observed in blood leukocytes from healthy volunteers incubated with clozapine (1 µM) (92). It has also been reported that, in Wistar rats, clozapine (45 mg/kg/day) induced myocarditis related with lymphocytic infiltrates, which induced the release of reactive oxygen species (ROS), cytokines, and TNF-α (93).…”
Section: Clozapinesupporting
confidence: 57%
“…In studies carried out in animal models, similar effects to those described above in cell cultures have been observed in MQs. In a perinatal phencyclidine rat model, the administration of clozapine increased IL-6 and TNF-α with sex-specific changes (91), which can fit in the theory of "cytokine signature" observed in blood leukocytes from healthy volunteers incubated with clozapine (1 µM) (92). It has also been reported that, in Wistar rats, clozapine (45 mg/kg/day) induced myocarditis related with lymphocytic infiltrates, which induced the release of reactive oxygen species (ROS), cytokines, and TNF-α (93).…”
Section: Clozapinesupporting
confidence: 57%
“…In our previous research, clozapine (1 mg/kg) administration for two consecutive weeks could up-regulate rat serum IL-6 levels but had no effect on serum TNF-α (Liu et al 2015). Some evidence suggests that the cytokines secretion upon chronic administration of clozapine (20 mg/kg/day) is gender dependent: serum IL-6 and TNF-α increased in female rats, but only serum TNF-α level increased in male rats (Nikolić et al 2017). Additionally, acute administration of clozapine inhibited the increase of serum TNF-α and IL-6 in lipopolysaccharidetreated mice (Sugino et al 2009).…”
Section: Discussionmentioning
confidence: 91%
“…As aforementioned, clozapine may be able to protect BMD by activating NMDARs; however, other mechanisms deserve attention too. A recent animal study showed that clozapine had protective effect on bones possibly via causing sex-specific increase in pro-inflammatory cytokines 30 . It will be interesting to explore the effect of clozapine on bone mass and other related parameters.…”
Section: Discussionmentioning
confidence: 99%